(untitled) (Engrami, 2022)
Based on the fact that journal ENGRAMI is indexed in Serbian citation index SCIndeks, which provides journal a check of the manuscript, we are informed that based on subsequent, retroactive manuscript checking on the presence of plagiarism by means of CrossRef/iThenticate service, a violation of academic ethical principles was found. The paper entitled: State of the art and new frontiers in sleep research: New qualitative and quantitative approaches by authors Ilanković N. and Ilanković A. (https://scindeks.ceon.rs/article.aspx?artid=0351-26650202062I) which is published in the journal ENGRAMI (2002): 24(2) (pp. 62-73) presents the (auto)plagiate (extensive use of the text published in the previous papers without quoting the original) of the articles: Ilanković N, Draganić S and Ilanković A. EEG and the sleep disorders. in: Ilanković N, Ilanković V. i Jašović-Gašić M. (eds). Bolesti spavanja dijagnostika i lečenje (Cibif, 1995): 79-96. Ilanković N and Ilanković AN. EEG and the Sleep Disorders: a new quantitative approach. In: Brain and Consciousness. Proceedings of the First Annual ECPD International Workshop on Scientific Bases of Consciousness. (Belgrade, 1997, Čigoja štampa), pp. 117-128. Moreover, paper “State of the art and new frontiers in sleep research: New qualitative and quantitative approaches” published in Engrami, 2002 was almost identical with the later publication: Ilanković N, Ilanković A, Ilanković V. New Hypothesis and Theory about Functions of Sleep and Dreams. Macedonian Journal of Medical Sciences. 2014 Mar 15; 7(1):78-82. The authors approached inadequately the quotation and citation of sources and thus acted contrary to the ethical code of scientific research, grossly violating the editorial policy of the journal ENGRAMI and Committee for Ethics of Publication principles. Bearing in mind a violation of ethical principles relating to a multiple submissions from 1995 to 2014, the editorial board of the journal ENGRAMI made a retraction of the paper.